Assessing Efficiency of Cloud-Based Services by the Method of Linear Programming; Applied Mechanics and Materials; Vol. 379 : Innovation materials and manufacturing technologies, economic aspects in enterprises - Razumnikov S. V. Sergey Viktorovich (Management and Economic Aspects in Enterprises, 2013)
Title screen